Commodore Edward Codrington in Catalonia during the Peninsular War (1810-1813) - Ramisa Verdaguer, Matías (Hispania Nova, 2021)
Captain Edward Codrington served between 1810 and 1813 off the coast of Catalonia, leading a squadron of the Royal Navy’s Mediterranean fleet. He aided the patriotic insurgents against the Napoleonic occupation. Apart from the warlike activity, Codrington became very involved in the political dynamics of the Principality, promoting radical liberalism. Perhaps for personal reasons and in contradiction to his ideology, he took sides against Captain General Luis Lacy and in favor of Baron de Eroles. His main idea was to arm all the people to fight the French and make a revolution. The article also describes the general framework of the situation in the Mediterranean and the personality of said naval captain.